2001
DOI: 10.1046/j.1365-2036.2001.01055.x
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of Crohn’s disease over 12 months: fixed versus flexible dosing regimen using budesonide controlled ileal release capsules

Abstract: Background: It may be possible to achieve more effective management of Crohn’s Disease by introducing a flexible dosage regimen sensitive to patients’ needs. Aim: Comparison of the efficacy and tolerability of a fixed vs. flexible budesonide controlled ileal release treatment regimen for the prevention and management of relapse in Crohn’s disease patients. Budesonide controlled ileal release is an oral formulation which delivers drug directly to disease sites in the ileum and ascending colon, by preventing mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 8 publications
0
18
0
Order By: Relevance
“…As these are meta-analyses, an additional trial has compared administration of a fixed dose of budesonide (6 mg daily) with a flexible dose (3-9 mg) for 12 months in 143 patients with inactive ileocaecal CD. 129 No significant difference was found. The average amount of budesonide received by the patients was comparable in the two groups.…”
Section: Corticosteroidsmentioning
confidence: 83%
“…As these are meta-analyses, an additional trial has compared administration of a fixed dose of budesonide (6 mg daily) with a flexible dose (3-9 mg) for 12 months in 143 patients with inactive ileocaecal CD. 129 No significant difference was found. The average amount of budesonide received by the patients was comparable in the two groups.…”
Section: Corticosteroidsmentioning
confidence: 83%
“…Oral budesonide capsules 6 mg/day are more effective than placebo or mesalamine 3 g/day for maintenance of remission in patients with steroid-dependent CD (24,25); and oral pH-modified release budesonide 6-18 mg/day is effective for the short-term maintenance of remission in patients with prednisolone-induced remission (26). Maintenance therapy with a variable dose of oral budesonide capsules at a dose of 0-9 mg/day to maintain symptomatic remission results in similar control of disease activity as oral budesonide capsules at a fixed dose of 6 mg/day (27) or prednisolone 0-40 mg/day adjusted to disease activity (28). Maintenance therapy with oral budesonide capsules 6-9 mg/day resulted in a similar clinical remission rate at 1 yr as azathioprine 2.2 mg/kg/day, but azathioprine resulted in greater endoscopic remission (29).…”
Section: Discussionmentioning
confidence: 99%
“…At the end of the study a decrease in steroid-related side effects together with recovery of adrenal function (which was impaired at baseline) were found in both the placebo and budesonide groups [42]. In a further study of 143 patients with CD in remission, a very low rate of relapse was found with administration of 6 mg/day budesonide maintenance treatment [43].…”
Section: Maintenance Of Remission and Preven-tion Of Post-operative Rmentioning
confidence: 84%